Modelo de evaluación institucional, basado en el enfoque sistémico, para valorar la calidad de la gestión de la institución educativa n° 80292 daniel alcides carrión de pango - otuzco - Aguilar Miguel, Arelis (2016)
The purpose of investigation was determining the quality of the step at the Educational Institution N 80292 Daniel Alcides Carrión of Pango – Otuzco, taking into account the model of institutional evaluation once the systemic focus was based on. In investigation he had in account the designs theoretic systemic and descriptico. Systemic theoretician to lay plans and to base the model and descriptico to appreciate the quality of the step. 11 teachers' sample was worked with and 10 family men, which were selected during a sampling not probabilistic, in the sole discretion of the investigator. Right after person under administration the corresponding questionnaires to the elements of the sample, it came to an end than the quality of the step of the teachers and family men, as to the raw materials, processes and the prone mailbag is worked out to regulate.